Controlled trial of ligation plus vasoconstrictor versus proton pump inhibitor in the control of acute esophageal variceal bleeding - Lo, Gin-Ho; Perng, Daw-Shyong; Chang, Chi-Yang; Tai, Chi-Ming; Wang, Huay-Min; Lin, Hui-Chen (Journal of gastroenterology and hepatology, 2013)
Background Endoscopic therapy combined with vasoconstrictor was generally recommended to treat acute variceal bleeding. However, up to 30% of patients may still encounter treatment failure. Objectives This trial was to evaluate the efficacy of combination with endoscopic variceal ligation (EVL) and proton pump inhibitor (PPI) infusion in patients with acute variceal bleeding. Methods Cirrhotic patients presenting with acute esophageal variceal bleeding were rescued by emergency EVL. Soon after arresting of bleeding varices, eligible subjects were randomized to two groups. Vasoconstrictor group received either somatostatin or terlipressin infusion. PPI group received either omeprazole or pantoprazole. End points were initial hemostasis, very early rebleeding rate, and adverse events. Results Sixty patients were enrolled in vasoconstrictor group and 58 patients in PPI group. Both groups were comparable in baseline data. Initial hemostasis was achieved in 98% in vasoconstrictor group and 100% in PPI group (P = 1.0). Very early rebleeding within 48–120 h occurred in one patient (2%) in vasoconstrictor group and one patient (2%) in the PPI group (P = 1.0). Treatment failure was 4% in vasoconstrictor group and 2% in PPI group (P = 0.95). Adverse events occurred in 33 patients (55%) in vasoconstrictor group and three patients (6%) in PPI group (P < 0.001). Two patients in vasoconstrictor group and one patient in PPI group encountered esophageal ulcer bleeding. Conclusions After successful control of acute variceal bleeding by EVL, adjuvant therapy with PPI infusion was similar to combination with vasoconstrictor infusion in terms of initial hemostasis, very early rebleeding rate, and associated with fewer adverse events.